Injury and depression among 212 039 individuals in 40 low- and middle-income countries. (2020) - Stickley, A.; Oh, H.; Sumiyoshi, T.; McKee, M.; Koyanagi, A.
Abstract: Aims: Although injuries have been linked to worse mental health, little is known about this association among the general population in low- and middle-income countries (LAMICs). This study examined the association between injuries and depression in 40 LAMICs that participated in the World Health Survey. Methods: Cross-sectional information was obtained from 212 039 community-based adults on the past 12-month experience of road traffic and other (non-traffic) injuries and depression, which was assessed using questions based on the World Mental Health Survey version of the Composite International Diagnostic Interview. Multivariable logistic regression analysis and meta-analysis were used to examine associations. Results: The overall prevalence (95% CI) of past 12-month traffic injury, other injury, and depression was 2.8% (2.6–3.0%), 4.8% (4.6–5.0%) and 7.4% (7.1–7.8%), respectively. The prevalence of traffic injuries [range 0.1% (Ethiopia) to 5.1% (Bangladesh)], and other (non-traffic) injuries [range 0.9% (Myanmar) to 12.1% (Kenya)] varied widely across countries. After adjusting for demographic variables, alcohol consumption and smoking, the pooled OR (95%CI) for depression among individuals experiencing traffic injury based on a meta-analysis was 1.72 (1.48–1.99), and 2.04 (1.85–2.24) for those with other injuries. There was little between-country heterogeneity in the association between either form of injury and depression, although for traffic injuries, significant heterogeneity was observed between groups by country-income level ( p = 0.043) where the pooled association was strongest in upper middle-income countries (OR = 2.37) and weakest in low-income countries (OR = 1.46). Conclusions: Alerting health care providers in LAMICs to the increased risk of worse mental health among injury survivors and establishing effective trauma treatment systems to reduce the detrimental effects of injury should now be prioritised.